Transcriptional landscape changes during human embryonic stem cell derivation. (17th September 2018) - Warrier, S; Taelman, J; Tilleman, L; Van der Jeught, M; Duggal, G; Lierman, S; Popovic, M; Van Soom, A; Peelman, L; Van Nieuwerburgh, F; Deforce, D; Chuva de Sousa Lopes, S M; et al.
Abstract: STUDY QUESTION: What are the transcriptional changes occurring during the human embryonic stem cell (hESC) derivation process, from the inner cell mass (ICM) to post-ICM intermediate stage (PICMI) to hESC stage, that have downstream effects on pluripotency states and differentiation? SUMMARY ANSWER: We reveal that although the PICMI is transcriptionally similar to the hESC profile and distinct from ICM, it exhibits upregulation of primordial germ cell (PGC) markers, dependence on leukemia inhibitory factor (LIF) signaling, upregulation of naïve pluripotency-specific signaling networks and appears to be an intermediate switching point from naïve to primed pluripotency. WHAT IS KNOWN ALREADY: It is currently known that the PICMI exhibits markers of early and late-epiblast stage. It is suggested that hESCs acquire primed pluripotency features due to the upregulation of post-implantation genes in the PICMI which renders them predisposed towards differentiation cues. Despite this current knowledge, the transcriptional landscape changes during hESC derivation from ICM to hESC and the effect of PICMI on pluripotent state is still not well defined. STUDY DESIGN, SIZE, DURATION: To gain insight into the signaling mechanisms that may govern the ICM to PICMI to hESC transition, comparative RNA sequencing (RNA-seq) analysis was performed on preimplantation ICMs, PICMIs and hESCs in biological and technical triplicates ( n = 3). PARTICIPANTS/MATERIALS, SETTING, AND METHODS: Primed hESCs (XX) were maintained in feeder-free culture conditions on Matrigel for two passages and approximately 50 cells were collected in biological and technical triplicates ( n = 3). For ICM sample collection, Day 3, frozen-thawed human embryos were cultured up to day five blastocyst stage and only good quality blastocysts were subjected to laser-assisted micromanipulation for ICM collection ( n = 3). Next, day six expanded blastocysts were cultured on mouse embryonic fibroblasts and manual dissection was performed on the PICMI outgrowths between post-plating Day 6 and Day 10 ( n = 3). Sequencing of these samples was performed on NextSeq500 and statistical analysis was performed using edgeR (false discovery rate (FDR) < 0.05). MAIN RESULTS AND THE ROLE OF CHANCE: Comparative RNA-seq data analysis revealed that 634 and 560 protein-coding genes were significantly up and downregulated in hESCs compared to ICM (FDR < 0.05), respectively. Upon ICM to PICMI transition, 471 genes were expressed significantly higher in the PICMI compared to ICM, while 296 genes were elevated in the ICM alone (FDR < 0.05). Principle component analysis showed that the ICM was completely distinct from the PICMI and hESCs while the latter two clustered in close proximity to each other. Increased expression of E-CADHERIN1 (CDH1) in ICM and intermediate levels in the PICMI was observed, while CDH2 was higher in hESCs, suggesting a role of extracellular matrix components in facilitating pluripotency transition during hESC derivation. The PICMI also showed regulation of naïve-specific LIF and bone morphogenetic protein signaling, differential regulation of primed pluripotency-specific fibroblast growth factor and NODAL signaling pathway components, upregulation of phosphatidylinositol 3-kinase (PI3K)/AKT/mammalian target of rapamycin (mTOR) pathway (PI3K/AKT/mTORC), as well as predisposition towards the germ cell lineage, further confirmed by gene ontology analysis. Hence, the data suggest that the PICMI may serve as an intermediate pluripotency stage which, when subjected to an appropriate culture niche, could aid in enhancing naïve hESC derivation and germ cell differentiation efficiency. LARGE-SCALE DATA: Gene Expression Omnibus (GEO) Accession number GSE119378. LIMITATIONS, REASONS FOR CAUTION: Owing to the limitation in sample availability, the sex of ICM and PICMI have not been taken into consideration. Obtaining cells from the ICM and maintaining them in culture is not feasible as it will hamper the formation of PICMI and hESC derivation. Single-cell quantitative real-time PCR on low ICM and PICMI cell numbers, although challenging due to limited availability of human embryos, will be advantageous to further corroborate the RNA-seq data on transcriptional changes during hESC derivation process. WIDER IMPLICATIONS OF THE FINDINGS: We elucidate the dynamics of transcriptional network changes from the naïve ICM to the intermediate PICMI stage and finally the primed hESC lines. We provide an in-depth understanding of the PICMI and its role in conferring the type of pluripotent state which may have important downstream effects on differentiation, specifically towards the PGC lineage. This knowledge contributes to our limited understanding of the true nature of the human pluripotent state in vitro . STUDY FUNDING/COMPETING INTEREST(S): This research is supported by the Concerted Research Actions funding from Bijzonder Onderzoeksfonds University Ghent (BOF GOA 01G01112).The authors declare no conflict of interest.